Comparative analysis of database access performance of the Hibernate framework and the Jooq library - Karol Hetman; Marek Miłosz (Journal of Computer Sciences Institute, 2025)
The subject of this paper was a comparative performance analysis of accessing relational databases in Java using two major Java libraries: Hibernate and jOOQ. For Hibernate, the main focus was on queries written with CriteriaBuilder. The study concentrated on key performance metrics, such as operation execution times and the number of operations processed per unit of time for DQL and DML operations. The measurements were conducted using the JMH library. The jOOQ library proved to be more efficient for simple and complex queries.